An ingestigation of the influence of bilateral deficit on the counter-movement jump performance in elite sprinters - Bracic, M.; Supej, M.; Peharec, S.; Bacic, P.; Coh, M. (Kinesiology, 2010)
The purpose of the present study was to investigate the bilateral deficit (BLD) in elite sprinters and examine the relationship between the BLD and sprint start performance. Twelve male elite sprinters (age: 22.41±3.39 years, 100m personal best: 10.82±.25s) performed sprint starts, two- and one-leg counter- -movement jumps (CMJ). A system of eight CCD cameras with a frequency of 200 Hz was used for the 3D kinematic measurements of CMJ. The ground reaction forces of sprint starts and vertical jumps were measured unilaterally and bilaterally by means of two independent and synchronized force platforms. Significantly lower values of force production of the front leg in the double start compared to the force production in the single start indicated the existence of a phenomenon similar to the bilateral deficit (BLD). The main findings of the present study were that: 1) lower values of BLD in the CMJ are related to higher peak force production of the rear leg in the double start of the sprint start (r=-.630; p=.000), 2) lower BLD in the CMJ is also related to higher total impulse of force on the blocks (r=-.550; p=.000) and 3) BLD values in CMJ are higher in elite sprinters compared to team sport athletes examined in the previous studies. The BLD measured in CMJ is a good indicator of a lower performance in the sprint start. As a consequence, the sprinters with higher BLD produced a lower total impulse of force on the blocks and lower block velocity, which are related to the overall 60m and 100m sprint performance.